2012
DOI: 10.1016/j.jff.2012.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Hibiscus sabdariffa L. extracts reduce serum uric acid levels in oxonate-induced rats

Abstract: Hibiscus sabdariffa extractOxonic acid Uricase Xanthine oxidase A B S T R A C T Elevated serum levels of uric acid are associated with an increased risk for hyperuricemia, gout, hypertension, cardiovascular disease, and renal failure. Recent attention has focused on the bioactive properties of edible plants in preventing disease. Hibiscus sabdariffa L., a local soft drink material and medicinal herb in Taiwan, is used effectively in native medicines against hypertension, pyrexia, and liver disorders. We invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 37 publications
0
22
0
2
Order By: Relevance
“…Studies carried out in animals and humans have primarily demonstrated either no change or decreases in measures related to function of the liver (AST and ALT liver enzymes [16, 46, 47]) or kidney (creatinine [16, 18, 22, 23, 31, 46, 48], blood urea nitrogen [18, 31], and urea [16]) function (Table 1). However, at doses of 300 mg/kg/day of HS over a 3 month period, an adverse effect on liver enzymes was observed, suggesting that at very high doses the extract could be hepatotoxic [46].…”
Section: Safety and Toxicitymentioning
confidence: 99%
“…Studies carried out in animals and humans have primarily demonstrated either no change or decreases in measures related to function of the liver (AST and ALT liver enzymes [16, 46, 47]) or kidney (creatinine [16, 18, 22, 23, 31, 46, 48], blood urea nitrogen [18, 31], and urea [16]) function (Table 1). However, at doses of 300 mg/kg/day of HS over a 3 month period, an adverse effect on liver enzymes was observed, suggesting that at very high doses the extract could be hepatotoxic [46].…”
Section: Safety and Toxicitymentioning
confidence: 99%
“…has been believed for many years to be able to reduce the risk of degenerative diseases. Several studies have shown that roselle was effective in lowering blood pressure ( [11]; [12]; [13]; [14]; [15]), had an antioxidant function protecting the liver from a damage ( [16]; [17]; [18]; [19]), increased the antioxidant enzymes in the liver [20], was anti-inflammatory and analgesic [21], and was found to lower uric acid ( [22]; [23]). Roselle has high antioxidant content.…”
Section: Introductionmentioning
confidence: 99%
“…The extract effectively inhibited hyperuricemia by increasing uricase activity and by decreasing serum uric acid levels. The XO activity was not affected by the extract [10].…”
Section: Malvaceaementioning
confidence: 81%
“…New agents such as uricase analogs and biological cytokine inhibitors have been also used for the treatment of gout [7,8]. Allopurinol, a commonly used XO inhibitor, has various adverse effects such as hypersensitivity syndrome, Stevens Johnson syndrome, renal toxicity, and fatal liver necrosis [9,10]. Gastric and renal adverse effects are common with long-term use of anti-inflammatory agents.…”
Section: Conventional Treatment Strategies and Associated Side Effectsmentioning
confidence: 99%
See 1 more Smart Citation